2015
DOI: 10.1007/s00300-015-1645-8
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and composition of the epibenthic megafauna north of Svalbard (Arctic)

Abstract: Benthic communities north of Svalbard are less investigated than in other Arctic shelf regions, as this area was covered by sea-ice during most of the year. Improving our knowledge on this region is timely, however, since climate change is strongly evident there, particularly with regard to the extent of sea-ice decline and its huge ecological impact on all marine biota, including the benthos. Moreover, longer ice-free periods will certainly lead to an increase in human activity levels in the area, including b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 54 publications
2
13
2
Order By: Relevance
“…In general, much of the same taxa composition was observed in both dives for depth zones below the sill depth. The largest difference in megabenthic community composition was found between the deepest and shallowest zones for both dives, and similar trends have been observed in other surveys (Starmans et al, 1999;Sswat et al, 2015;Molina et al, 2019). In the present study, the Basin Zone was characterized more by sessile fauna (e.g., P. squamatus, Acesta excavata, Hymenodiscus coronata, and sponges) and M. tenuimana, whereas the Above Sill Zone was more dominated by echinoderms and anemones.…”
Section: Community Patterns With Depth and Distance From The Sillsupporting
confidence: 90%
“…In general, much of the same taxa composition was observed in both dives for depth zones below the sill depth. The largest difference in megabenthic community composition was found between the deepest and shallowest zones for both dives, and similar trends have been observed in other surveys (Starmans et al, 1999;Sswat et al, 2015;Molina et al, 2019). In the present study, the Basin Zone was characterized more by sessile fauna (e.g., P. squamatus, Acesta excavata, Hymenodiscus coronata, and sponges) and M. tenuimana, whereas the Above Sill Zone was more dominated by echinoderms and anemones.…”
Section: Community Patterns With Depth and Distance From The Sillsupporting
confidence: 90%
“…Lateral advection is also responsible for local-scale patterns of benthic food supply (Mayer and Piepenburg, 1996;Piepenburg, 2005). In a recent study, (Sswat et al, 2015) found that the north Svalbard shelf benthos was influenced by depth and substratum type, with higher diversity and abundance of sessile suspension feeders occurring at shallower stations. Station 14 in this case study had the highest abundance and diversity of suspension feeders and also the greatest availability of hard substrata (Figures 5, 9).…”
Section: Discussionmentioning
confidence: 99%
“…Despite recent research efforts (Sswat et al, 2015), our understanding of how abiotic factors influence the megabenthos around Svalbard remains limited. As future climatic changes are likely to be more dramatic in the Arctic than in other regions (ACIA, 2006;Mora et al, 2013), it is especially important to understand what factors influence these communities (Bergmann et al, 2011;Nephin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Their highest litter counts coincide with areas of intensive fishery and shipping. Indeed, Sswat et al (2015) reported evidence of trawling activities at all stations [300 m depth on the seabed northwest of Svalbard.…”
Section: Discussionmentioning
confidence: 99%